The Effect Of The Project-Based Learning Model Assisted By Blended Learning On The Critical Thinking Ability Of Grade VIII Students at SMP Negeri 04 Paleleh Barat - Arianti Masanggelo; Orbanus Naharia; Mariana Rengkuan (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study was undertaken in response to the deficient cognitive abilities of students. The problem in this study is whether there is an influence of the project-based learning (PjBL) model, which is assisted by blended learning, on improving students' critical thinking skills in class VIII of SMP Negeri 04 Paleleh Barat. This study aims to determine whether the project-based learning (PjBL) model is assisted by blended learning in students' critical thinking skills in class VIII of SMP Negeri 04 Paleleh Barat. This study was performed in SMP Negeri 04 Paleleh Barat between April to May 2024, employing a quasi-experimental methodology. The sample in this study consisted of class VIII-A as the experimental group and class VIII-B as the control group. Both classes will undergo a learning outcome assessment comprising a pretest and a posttest. The data analysis revealed that the project-based learning (PjBL) paradigm, augmented by blended learning, significantly influenced students' critical thinking skills on the human excretory system in class VIII at SMP Negeri 04 Paleleh Barat. This is derived from the t-test results obtained using IBM SPSS for Windows version 2.2, with a significance value. If the p-value (2-tailed) is less than the significance level (alpha) of 0.05, specifically 0.002 < 0.05, then the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted.